(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Introduction. A key feature of the enterprise marketing management is the implementation of management marketing concepts, ideas and approaches in all functional areas of business organization and enterprise management. Marketing management of the enterprise is carried out through the use of resources and marketing technologies. The purpose of the article. The purpose of the article is to determine the nature, content and features of the use of marketing resources and technologies in the enterprise marketing management. Results. It is determined that marketing resources should be defined as the means of the enterprise, which allow to form an effective system of creating ideas and goods or services, their pricing, promotion, distribution and help to improve the image of the enterprise and consumer loyalty. Hence, marketing resources are a set of interconnected and interdependent tools that are available and aimed at producing goods and services that have value for consumers and are able to meet their needs at the best price and at the same time make a profit. It is substantiated that marketing technologies should be considered in a broad sense as a set or model of consistent marketing processes, techniques, actions and a system of scientific knowledge about them, while in a narrower semantic aspect, as a set of marketing tools that are used in the marketing activity of the enterprise. In modern conditions, effective operation of the enterprise involves active use of marketing resources, tools and technologies aimed to achieve social and economic goals of its activities. Marketing tools combined in the marketing technology enable to effectively address issues related to the development, distribution and consumption of goods and services. Conclusions. Marketing resources and technologies play an important role in the establishment, operation and development of any enterprise. Their competent use enables to improve the level of the enterprise management, increase the competitiveness of the enterprise and its products on the market. Effective market activity and successful competition require that the management of enterprises have knowledge and competencies for the optimal use of marketing resources and use technologies for marketing activities.